The Effect Of Electronic Word Of Mouth, Self Congruity And Brand Awareness On E-Purchase Intention In Crsl Brands (Survey On Tiktok Shop User Students In Sleman Regency, Yogyakarta) - Anastasia Ines Chyntia Putri; Surpiko Hapsoro Darpito; Hadi Oetomo; Hery Sutanto (Journal of International Conference Proceedings, 2024)
This study aims to determine the effect of electronic word of mouth (eWOM), self-congruity, and brand awareness on e-purchase intention for the CRSL brand. The data collection technique employed is non-probability sampling with a purposive sampling method. The data analysis method in this study uses multiple regression analysis techniques through SPSS 23. This research adopts a causal associative design using a quantitative approach. The population in this study consists of all students who use TikTok Shop and are familiar with the CRSL brand in Sleman Regency, Yogyakarta. The sample size used in this study is 100 respondents. The results reveal that eWOM, self-congruity, and brand awareness collectively have a positive and significant effect on e-purchase intention. Furthermore, eWOM individually has a positive and significant effect on e-purchase intention, self-congruity has a positive and significant effect on e-purchase intention, and brand awareness also has a positive and significant effect on e-purchase intention